Contemporaray political thought. A Reader and guide - FINLAYSON, Alan (Edinburgh University Press, 2003)
Contemporary Political Thought is a foundation textbook in political thought. It brings together readings by leading exponents of contemporary political theory with lucid, jargon-free introductions, and is the first book in the area to combine these pedagogical elements.